2023
DOI: 10.3390/medicina59061025
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Serum Amyloid A as a Marker of Preterm Birth/PROM: A Systematic Review and Meta-Analysis

Ioana-Evelina Chiriac,
Narcis Vilceanu,
Adrian Maghiar
et al.

Abstract: Background and Objectives: Preterm birth, one of the leading causes of neonatal mortality, occurs in between 5 and 18% of births. Premature birth can be induced by a variety of triggers, including infection or inflammation. Serum amyloid A, a family of apolipoproteins, increases significantly and rapidly at the onset of inflammation. This study aims to systematically review the results of studies in the literature that have examined the correlation between SAA and PTB/PROM. Materials and Methods: To examine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
(67 reference statements)
0
1
0
Order By: Relevance
“…When the body is injured and inflammation occurs, the SAA level increases and regulates the adhesion, migration, proliferation and aggregation of cells [ 40 ]. Interestingly, others found that elevated SAA levels may be related to abnormalities in the decidualization process, which may lead to maternal infertility or spontaneous abortion [ 41 ]. Therefore, further functional experiments are required to elucidate the role of SAA in the early pregnancy of ewes.…”
Section: Discussionmentioning
confidence: 99%
“…When the body is injured and inflammation occurs, the SAA level increases and regulates the adhesion, migration, proliferation and aggregation of cells [ 40 ]. Interestingly, others found that elevated SAA levels may be related to abnormalities in the decidualization process, which may lead to maternal infertility or spontaneous abortion [ 41 ]. Therefore, further functional experiments are required to elucidate the role of SAA in the early pregnancy of ewes.…”
Section: Discussionmentioning
confidence: 99%